Enhancing hospital planning capacity and resilience in crisis scenarios using interpretive structural modeling (ISM) - Junsong, Bai (2023)
Hospitals are the critical support infrastructures. In the confrontation with natural disasters, infectious diseases, and other crises that severely affect the supply and demand of local medical services—and even jeopardize the hospital itself—, the hospital needs first to secure the essential emergency functions and, secondly, to recover from the impact as quickly as possible. Hospital resilience has numerous influencing elements and evaluation criteria, but there are still ambiguous boundaries in their internal influence relationships and hierarchical structures. Therefore, this study explores the determinants and pathways of practice for strengthening hospital resilience from an internal management perspective, applying Group Decision Making and Interpretive Structural Modeling (ISM) to pool the knowledge and experience of experts in related fields and identify critical variables. Based on the information collected and analyzed, a hierarchical model of hospital resilience was established. The results and practical applicability of the model were then validated by external experts to provide new knowledge for the development of hospital resilience management.